A general non-orthogonal collocated finite volume algorithm for turbulent flow at all speeds incorporating second-moment turbulence-transport closure, Part 2: Application - Lien, F.S; Leschziner, M.A (Computer methods in applied mechanics and engineering, 1994)
A general non-orthogonal finite-volume procedure, documented in a companion paper presented earlier, is applied to six flows, one 2D laminar, one 2D turbulent, two 3D turbulent, one inviscid transonic and one turbulent transonic. The principal aim is to convey the capabilities of the method, and this aim is pursued by choosing flows which feature a wide range of phenomena and processes. In some cases, a comparison is presented between two or more turbulence-modelling practices, and in these cases, considerable emphasis is put on an analysis of model performance and associated physical implications.